Diversity‐Oriented Synthesis of α‐Functionalized Acylborons and Borylated Heteroarenes by Nucleophilic Ring Opening of α‐Chloroepoxyboronates. Issue 39 (21st August 2019) - Tan, Dong‐Hang; Cai, Yuan‐Hong; Zeng, Yao‐Fu; Lv, Wen‐Xin; Yang, Ling; Li, Qingjiang; Wang, Honggen
Abstract: The ring‐opening reactions of N ‐methyliminodiacetyl (MIDA) α‐chloroepoxyboronates with different nucleophiles allow the modular synthesis of a diverse array of organoboronates. These include seven types of α‐functionalized acylboronates and seven types of borylated heteroarenes, some of which are difficult‐to‐access products using alternative methods. The common synthons, α‐chloroepoxyboronates, could be viably synthesized by a two‐step procedure from the corresponding alkenyl MIDA boronates. Mild reaction conditions, good functional‐group tolerance, and generally good efficiency were observed. The utility of the products was also demonstrated. Abstract : The nucleophilic ring‐opening reactions of N ‐methyliminodiacetyl (MIDA) α‐chloroepoxyboronates, a new synthon prepared by a two‐step procedure from alkenyl MIDA boronates, lead to the facile synthesis of α‐functionalized acylboronates and borylated heteroarenes in a divergent manner. Some of the products are difficult to access by alternative methods.